Genomic characterisation and ecological distribution of Mantoniella tinhauana: a novel Mamiellophycean green alga from the Western Pacific - Rey Redondo, Elvira; Xu, Yangbing; Yung, Charmaine Cheuk Man (Frontiers in Microbiology, 2024)
Mamiellophyceae are dominant marine algae in much of the ocean, the most prevalent genera belonging to the order Mamiellales: Micromonas, Ostreococcus and Bathycoccus, whose genetics and global distributions have been extensively studied. Conversely, the genus Mantoniella, despite its potential ecological importance, remains relatively undercharacterised. In this study, we isolated and characterised a novel species of Mamiellophyceae, Mantoniella tinhauana, from subtropical coastal waters in the South China Sea. Morphologically, it resembles other Mantoniella species; however, a comparative analysis of the 18S and ITS2 marker genes revealed its genetic distinctiveness. Furthermore, we sequenced and assembled the first genome of Mantoniella tinhauana, uncovering significant differences from previously studied Mamiellophyceae species. Notably, the genome lacked any detectable outlier chromosomes and exhibited numerous unique orthogroups. We explored gene groups associated with meiosis, scale and flagella formation, shedding light on species divergence, yet further investigation is warranted. To elucidate the biogeography of Mantoniella tinhauana, we conducted a comprehensive analysis using global metagenomic read mapping to the newly sequenced genome. Our findings indicate this species exhibits a cosmopolitan distribution with a low-level prevalence worldwide. Understanding the intricate dynamics between Mamiellophyceae and the environment is crucial for comprehending their impact on the ocean ecosystem and accurately predicting their response to forthcoming environmental changes.